Consensus statement on placebo effects in sports and exercise: The need for conceptual clarity, methodological rigour, and the elucidation of neurobiological mechanisms - Beedie, C; Benedetti, F; Barbiani, D; Camerone, E; Cohen, E; Coleman, D; Davis, A; Edelesten, C; Flowers, E; Foad, A; Harvey, S; Hettinga, F; et al. (Taylor and Francis, 2018)
In June 2017 a group of experts in anthropology, biology, kinesiology, neuroscience, physiology, and psychology convened in Canterbury, UK, to address questions relating to the placebo effect in sport and exercise. The event was supported exclusively by Quality Related (QR) funding from the Higher Education Funding Council for England (HEFCE). The funder did not influence the content or conclusions of the group. No competing interests were declared by any delegate. During the meeting and in follow-up correspondence, all delegates agreed the need to communicate the outcomes of the meeting via a brief consensus statement. The two specific aims of this statement are to encourage researchers in sport and exercise science to 1. Where possible, adopt research methods that more effectively elucidate the role of the brain in mediating the effects of treatments and interventions. 2. Where possible, adopt methods that factor for and/or quantify placebo effects that could explain a percentage of inter-individual variability in response to treatments and intervention.